Working in Partnership to Build Placement Capacity in a Competitive World - Blenkin, Dawn; Bedding, Nina (International Journal of Practice-based Learning in Health and Social Care, 2017)
A number of higher education institutions (HEIs) report continual issues with placement cancellations due to a lack of commitment at practitioner level. Whilst there is a professional requirement to contribute to student education, it has been difficult to enforce accountability on autonomous practitioners. The culture of sourcing and allocating placements is problematic. As occupational therapists who supported student education in the NHS and Social Care, we have now become responsible for organising placement education opportunities for a HEI. This has provided a privileged insight into the differing cultures, expectations, and issues inherent to this collaboration. Tasked with making placement provision an attractive and quality experience through collaborative working in a competitive world, a new way of working was found to be required. In this reflective paper, we consider an allocation model as a method of building placement capacity whilst challenging cultural norms. The model has been successfully implemented, and is now in its third year of implementation. This new placement capacity model has reduced the time spent sourcing and allocating placements. Additionally, the number of cancellations has become negligible whilst the choice of placements for the HEI has increased.